2015
DOI: 10.1002/jccs.201500348
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amino Acid‐comprising Sialyltransferase Inhibitors and Their Antimetastatic Activities against Human Breast Cancer Cells

Abstract: The amino acid-containing lithocholic acids (LCA) represent a new class of human sialyltransferase (ST) inhibitors. In this study, we have reported their design, synthesis, and inhibitory activity against human STs. Among these derivatives, D-Glu-LCA 7, L-Asp-L-Asp-LCA 13, and L-Asp-L-Asp-Gly-Gly-LCA 22 with specific amino acid sequence were the most active ones with IC 50 values of 2.3-5.6 and 4.2-6.2 mM toward a-2,3-ST and a-2,6-ST, respectively. The current study demonstrates that the new class of ST inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The complete structure–activity relationship and optimization are depicted in Figure S1. Our initial studies focused on the effect of C(3) amino acid moiety and observed LCA with a specific amino acid sequence, such as l -Asp-LCA, l -Glu-LCA, d -Glu-LCA, l -Asp- l -Asp-LCA, and l -Asp- l -Asp-Gly-Gly-LCA, displaying potent inhibitory activity against human STs, α2,3- N -ST, and α2,6- N -ST, respectively. , Building on the optimal structure of L-Asp-LCA, we extended the additional groups in the N-terminal of Asp and found the heterocyclic moiety (NBD, NP, and MC) exhibiting greater inhibitory activities against α2,3- N -ST, α2,3- O -ST, and α2,6- N -ST compared to that of L-Asp-LCA (Lith- O -Asp), suggesting that perhaps a heterocyclic moiety at the N-terminal position could occupy an interactive region in the active site pocket of ST isozyme. For example, AL10, possessing an NBD group at the N-terminal position, displayed improved inhibitory potency against α2,3- N -ST, α2,3- O -ST, and α2,6- N -ST with respective IC 50 values of 0.9, 13.2, and 1.5 μM (Table ), which are with 3–13-fold increased potency over l -Asp-LCA (Lith- O -Asp).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete structure–activity relationship and optimization are depicted in Figure S1. Our initial studies focused on the effect of C(3) amino acid moiety and observed LCA with a specific amino acid sequence, such as l -Asp-LCA, l -Glu-LCA, d -Glu-LCA, l -Asp- l -Asp-LCA, and l -Asp- l -Asp-Gly-Gly-LCA, displaying potent inhibitory activity against human STs, α2,3- N -ST, and α2,6- N -ST, respectively. , Building on the optimal structure of L-Asp-LCA, we extended the additional groups in the N-terminal of Asp and found the heterocyclic moiety (NBD, NP, and MC) exhibiting greater inhibitory activities against α2,3- N -ST, α2,3- O -ST, and α2,6- N -ST compared to that of L-Asp-LCA (Lith- O -Asp), suggesting that perhaps a heterocyclic moiety at the N-terminal position could occupy an interactive region in the active site pocket of ST isozyme. For example, AL10, possessing an NBD group at the N-terminal position, displayed improved inhibitory potency against α2,3- N -ST, α2,3- O -ST, and α2,6- N -ST with respective IC 50 values of 0.9, 13.2, and 1.5 μM (Table ), which are with 3–13-fold increased potency over l -Asp-LCA (Lith- O -Asp).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Despite ample documentation of the importance of post-translational sialylation of glycoproteins and glycolipids to the regulation of immune cells or cell–cell adhesion and to the regulation of tumor cell metastasis and invasion, an inhibitor with ST isozyme preference has yet to be identified for application in in vitro studies or for in vivo use to repress cancer metastasis. With few exceptions, inhibitor designs have concentrated on creating tight-binding substrate analogues. Because most of these inhibitors are not cell permeable, their use in biological and clinical applications is restricted. To overcome the availability of STs, recent advances in the design of various expression systems for recombinant enzyme production open up the opportunity to screen compounds against a wider panel of ST enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, classic cytotoxicity tests such as MTT and MTS assays have shown very little to no toxicity for a range of ST inhibitors, which greatly enhances their drug development potential . Thus, the most prevalent assays in this area are those that measure cell invasion; cell migration using Transwell chamber migration assays; and cell adhesion to plates coated in collagen IV, fibronectin, or laminin, along with traditional wound healing assays . Further antimetastasis assays include those that assess activation of integrins and downstream mediators of integrin signaling, such as FAK (focal adhesion kinase), and PI3K/Akt signaling via Western blot analysis .…”
Section: Biological Assaysmentioning
confidence: 99%
“…The test of the antimetastatic effect of AL‐10 in vivo revealed a 40% reduction of lung metastasis in serum biochemical assays. More recently, further derivatives have been prepared based on the encouraging results observed with the Lith‐ O ‐amino acid compounds . Therefore, short peptidic units were attached to the 3‐ O ‐position of the steroid moiety.…”
Section: Sialyltransferase Inhibitorsmentioning
confidence: 99%